Cash waqf as an instrument for sustainable islamic education development in Indonesia - Anjar Mahmudin Nst (RedWhite Press, 2024)
This study aims to analyze the concept and implementation of cash waqf in financing Islamic education, examine its contribution to the independence and sustainability of Islamic educational institutions, and formulate strategies for optimizing cash waqf in Indonesia. This research employs a qualitative approach through library research. Data were collected from books, scientific journals, legislation, and various relevant documents concerning waqf and Islamic education. The findings indicate that cash waqf possesses significant potential as a sustainable financing source for Islamic educational institutions. Through productive, transparent, and professional management, cash waqf can support operational costs, educational infrastructure development, scholarships, and institutional empowerment. Moreover, cash waqf contributes to reducing educational dependence on government funding and strengthens the economic resilience of Islamic educational institutions. The optimization of cash waqf requires regulatory support, professional nazhir management, digitalization, community participation, and synergy among stakeholders. This study concludes that cash waqf can serve as a strategic instrument for strengthening the sustainability and quality of Islamic education in Indonesia.